Pelagiaria (Teleostei: Acanthomorpha) as a non-analogue adaptive radiation - Beckett, H (2018)
Pelagiaria is an anatomically disparate clade of open-ocean fishes identified through molecular studies, comprising 16 families not previously united on the basis of morphology. It has been postulated that ecologically distinct lineages of Pelagiaria diverged rapidly early in the Paleogene. This differs from ‘model’ adaptive radiations like cichlid fishes and Anolis lizards in age and geographic scale, but corresponds closely to patterns in Cenozoic mammals, the group where the concept was first defined. Well-preserved material from the UK, Angola and other sites provides an opportunity to investigate the evolutionary history of Pelagiaria and test these hypotheses of adaptive radiation. I use micro computed tomography (μCT) to investigate key three-dimensionally preserved fossils belonging to groups now assigned to Pelagiaria, focussing on scombrids (tunas, mackerels) and trichiuroids (snake mackerels). I develop character sets for trichiuroids and scombrids, allowing placement of key fossils associated with these groups. I also use μCT to collect three-dimensional cranial landmark data from 68 extant species of Pelagiaria, representing 15/16 extant families and a quarter of living species. These phenotypic data are studied in combination with a time-calibrated molecular phylogeny, which I apply using multiple comparative approaches. Results indicate that Pelagiaria showed an initial, diffusive phase of phenotypic evolution in the early Paleogene, followed by constrained patterns of cranial change from the Eocene onward. This adds quantitative support to previous hypotheses of adaptive radiation in the group, and suggest Pelagiaria might represent a useful a new study system for investigating this key macroevolutionary concept.